Me too! A case study of gendered victimization and feminist development in a Swedish peer support organization for people with experiences of criminalization and substance abuse - Bäcklin, Emy (Frontiers in Psychiatry, 2022)
Even if peer support is commonly defined as horizontal in contrast to the more hierarchical relationship between client and professional, peer support is not free from power dynamics. This article considers feminist organizing in the context of peer support for people with experiences of criminalization and substance abuse and addresses questions of (un)equal peer support, sexual victimization, reintegration, and organizational change in the #MeToo era. Drawing on qualitative interviews with support organization representatives and discussion material from a study circle and a men’s group, this article analyses one organization’s framing of, and responses to, allegations of sexual victimization of female members, and their ongoing work towards increased equality. The study shows that a number of measures has been taken in the organization in order to give voice to women whose livelihoods are affected by crime, imprisonment, violence, and drug abuse. Interview participants put strong emphasis on the need to counteract what is described as a “macho culture” embedded in the peer support organization (PESO), which is seen as repeating structures of masculinity and power from the previous criminal lifestyle as well as reproducing vulnerabilities that the female members have experienced before they entered the PESO. The organization’s patriarchal structure is understood as connected to a culture of silence that have allowed for sexism and marginalization of female members to continue. The study’s focus on women’s lived experiences of trauma within peer support practices and their struggles to redefine the foundations of their organization emphasizes the lived gendered emotionality of peer support.